The relationship of diet quality and body composition with depression level in young women - Hülya Yardımcı; Gülperi Demir (Acta Scientiarum. Health Sciences, 2022)
The purpose of this study was to determine how effective diet quality and body composition are in determining depression level among university-age female students. The study was designed as a cross-sectional study and conducted on 105 university female students (mean±SD, 20.3±1.9 years old). Data were collected in face-to-face interviews using questionnaire. The statistical analysis was performed with SPSS 23.0. Univariate and multiple regression analysis was performed to determine the association between participants' BDI levels and diet quality and anthropometric measurements. It was determined that 46.7% had mild and 25.7% had moderate/severe depression symptoms (mean BDI score: 13.6±7.0). Depression scores of young women were positively affected by BMI, waist circumference, waist / height ratio, fat ratio values, and negatively affected by muscle mass (p< .05). The depression scores of young women were positively affected by the NAR energy and NAR carbohydrate scores (p< .05). The iron, calcium and omega 3 NAR scores of young women affected the depression score significantly and negatively (p< .05). This study showed that diet quality was effective in keeping the body composition within the desired values, preventing depression and so enhancing the quality of life. Improving the diet quality is important for promoting the health status and life quality.